Constructed Wetlands for Reclamation and Reuse of Wastewater and Urban Stormwater: A Review - Biswal, Basanta Kumar; Balasubramanian, Rajasekhar (Frontiers in Environmental Science, 2022)
In recent years, increasing attention has been given for reclamation and reuse of water (wastewater and stormwater) in the context of augmenting water supplies. Constructed wetland (CW) systems make use of natural substrates, plants, and microbes for decontamination of wastewater and stormwater. These nature-based water treatment systems are cost-effective and sustainable. This review critically analyzes the recent advances on the application of CW systems for removal of total suspended solids (TSS), various chemical (nutrients including total nitrogen and total phosphorus, heavy metals, and organics) and microbial pollutants (Escherichia coli, enterococci, fecal coliforms, etc.) in wastewater and stormwater. Furthermore, the influence of key factors including CW configurations, substrates, vegetation, ambient temperature/seasonal changes, oxygen levels and hydraulic retention time on the performance of CW systems are discussed. Insights into various pollutant removal mechanisms, microbial diversity and modeling (kinetics, hydrological and mechanistic) are provided. CW systems show good performance for removal of diverse pollutants from wastewater and stormwater. The pollutant removal mechanisms include physical (sedimentation and filtration), chemical (sorption, complexation and precipitation) and biological (biodegradation, microbial transformation and microbial/plant assimilation) processes. The dominant microbial communities enriched in CW systems include nitrifiers, denitrifiers and organic biodegraders. The key knowledge gaps in the development of multifunctional CW systems are highlighted. We believe that this critical review would help urban planners, environmental engineers and managers with implementation of innovative strategies for wastewater and stormwater reclamation and reuse to alleviate water stress in urban areas and to contribute to environmental sustainability. Moreover, this review would help to optimize the performance of CW systems as well as to develop of regulatory guidelines for installation, operation and maintenance of CW systems.